IMPLIKASI ETIKA INJIL MATIUS BAGI KEHIDUPAN MORAL ORANG PERCAYA - Marlin Marlin; Susanti Salak, Natalia Lamba, Heriayanto, Mirsa Triwani (ADISAM PUBLISHER, 2025)
This article examines the ethical implications of the Gospel of Matthew for the moral lives of believers, emphasizing the relevance of Jesus' teachings in shaping Christian identity and witness. The ethics taught in the Gospel of Matthew, particularly through the Sermon on the Mount, provide a solid foundation for Christian morality rooted in the values of the Kingdom of God. This research employed a qualitative method through literature review, examining biblical texts, theological literature, and relevant academic studies. The results indicate that the ethics of the Kingdom of God is the moral foundation that guides believers to live in piety, justice, and truth. The dimensions of love and forgiveness form a relational ethic that builds a harmonious life together. Furthermore, the social responsibility emphasized by Matthew calls believers to act as salt and light of the world, making concrete contributions to creating justice and peace. Furthermore, the integration of faith and action is a key emphasis in Matthew's ethics, where true faith is manifested through concrete actions that reflect God's love. Thus, this article confirms that the ethics of the Gospel of Matthew is holistic, transformative, and relevant to the moral lives of believers, both in the personal and social spheres